THE EFFECT OF WORK STRESS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Allifiyah, Nadhifah Ayu; Ekowati, Vivin Maharani; Supriyanto, Achmad Sani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Many businesses operate in the same field, both small and large. Business competition, including catering services, is getting tighter and faster. High sales due to business competition indicate that performance will also be high, allowing employees to feel work stress and creating a less conducive work environment. This research examines the effect of work stress and work environment on employee performance at Duta Catering Batu City. This research uses quantitative methods with an Explanatory Research approach. The sample used was 70 people or the entire population, using a saturated sampling technique in nonprobability sampling, which was data collection using interviews and questionnaires. The questionnaire was administered using a Likert scale. At the same time, research data processing was carried out using SPSS (Statistical Program for Social Sciences) version 26 software and applying multiple linear regression analysis methods. The findings showed that work stress negatively and not significantly influenced employee performance at Duta Catering Batu City partially, while the work environment influenced employee performance positively and significantly. In addition, simultaneous testing shows that work stress and work environment jointly and significantly influenced employee performance.